The Effect of Socialization on the Implementation of the MBKM Curriculum Policy for Civil Engineering Students at Universitas Komputer Indonesia - Pratiwi, VItta (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
The goal of this study was to see how socialization affected the implementation of the "Merdeka Belajar Kampus Merdeka" (MBKM, Independent Campus Free to Learn) policy for students in the Engineering Department at Universitas Komputer Indonesia. The data from the SPADA DIKTI questionnaire results were mapped using quantitative methods and SWOT analysis with survey respondents from the Civil Engineering Department at Universitas Komputer Indonesia. The study's findings should provide an overview of the effect of socialization on student interest in participating in the MBKM Program. The MBKM questionnaire results show that respondents see a positive improvement in the MBKM policy, but the policy's weakness is the dissemination of MBKM information, which is still very limited. Poor socialization indicates that students' interest in participating is very low, as evidenced by the questionnaire results, which show that there is a small relationship between MBKM knowledge (63 percent) and student interest in the mediocre MBKM program (71.2 percent ). Although students are aware that MBKM provides benefits for increasing competence, soft skills, and benefits for the post-graduate period, threats such as funding concerns cause students to decline participation in the MBKM Program. Effective socialization is critical; socialization of MBKM implementation should use student-favored social media channels, because social media channels can influence the current generation more than information on the official website or channel of Higher Education.